Mechanical Properties and Performance Evaluation of High Density Polyethylene (HDPE)/Glass Fiber Composite - Lam , Zang Liang (IRC, 2018)

(untitled)
Polymer composite comprises of thermoplastic or thermoset polymer with inorganic fillers to develop the composite structure. The polymer acts as the matrix while the fillers are used as reinforcement. Interfacial bonding of HDPE and glass fiber reinforcement can be limited without the presence of maleic anhydride grafted polypropylene (MAPP) and mechanical properties of the HDPE/glass fiber composite are strongly affected by addition of MAPP as coupling agent. The objectives of the work were to evaluate mechanical properties of high density polyethylene (HDPE)/glass fiber composite with addition of MAPP and to compare and analyze the properties between different HDPE compositions. Mechanical properties of neat HDPE, 70/30 wt.% of HDPE/glass fiber composite, and 70/30 wt.% of HDPE/glass fiber composite with 5 wt.% of MAPP were evaluated based on tensile strength, flexural strength, flexural modulus, and impact strength. The samples were obtained through extrusion and injection molding process. The HDPE/glass fiber composites had higher mechanical properties compared to neat HDPE due to presence of coupling agent and glass fiber. The results showed that there was 72.4% increase in tensile strength from HDPE/glass fiber compared to neat HDPE whereas 95.6% increase in tensile strength from HDPE/glass fiber/MAPP compared to neat HDPE. HDPE/glass fiber/MAPP had the highest tensile strength of 44.0 MPa.